The protection of sulforaphane on subarachnoid hemorrhage-induced intestinal mucosa injury in rats - Liu, Zixiang; Li, Pengpeng; Zhang, Yuanhai; Zhao, Shidi; Gao, Wei (Frontiers in Molecular Biosciences, 2025)
IntroductionSulforaphane (SFN) is recognized for its anti-inflammatory properties; however, the underlying molecular mechanisms remain unclear. In this study, we explored the effect of SFN on subarachnoid hemorrhage (SAH) and the potential mechanisms.MethodsSprague–Dawley (SD) rats were divided into three groups (n = 12): Sham + vehicle group (Sham + V), SAH + vehicle group (SAH + V), and SAH + SFN group (SAH + S). SFN (50 mg/kg) dissolved in 250–280 μL corn oil was intraperitoneally injected, and the same volume of corn oil was served as the control. The appetite score, gut wet/dry weight ratio, and histological changes in ileum tissues were examined to determine intestinal mucosal injury. Quantitative real-time PCR (qRT-PCR) and Western blot were performed to examine the expression of genes. LC3 immunofluorescence and Hoechst 33258 staining were used to assess cell autophagy and apoptosis.ResultsCompared to the SAH + V group, the SAH + S group demonstrated a significantly increased appetite score (1.55 ± 0.23 vs. 1.90 ± 0.35); decreased gut wet/dry weight ratio (4.02 ± 0.21 vs. 3.18 ± 0.21) and inflammatory score (2.89 ± 0.33 vs. 1.89 ± 0.60); elevated mRNA expression of Nrf-2 (1.12 ± 0.14 vs. 1.89 ± 0.12), HO-1 (0.46 ± 0.02 vs. 1.02 ± 0.10), and NQO-1 (1.35 ± 0.09 vs. 1.97 ± 0.18); and elevated protein levels of Nrf-2 (0.92 ± 0.18 vs. 1.43 ± 0.23), Keap1 (0.31 ± 0.03 vs. 0.44 ± 0.02), HO-1 (0.65 ± 0.02 vs. 0.88 ± 0.02), NQO-1 (0.58 ± 0.02 vs. 0.78 ± 0.02), LC3-II/I (0.20 ± 0.004 vs. 0.28 ± 0.01), ATG4D (0.45 ± 0.01 vs. 0.72 ± 0.04), and P62 (0.85 ± 0.01 vs. 0.99 ± 0.03). The in vitro experiments further revealed that 3-methyladenine (3-MA) significantly reversed the decreased apoptosis of IEC-6 cells induced by 20 μmol/L SFN (20.60 ± 1.28 vs. 11.50 ± 0.58).ConclusionSFN exhibited the protective effect on intestinal mucosa injury after SAH via activating autophagy, which may provide an innovative approach to alleviate the intestinal mucosa injury caused by SAH.